Characterization of the immune related lncRNAs in bladder cancer to aid immunotherapy - Xiao, Ying; Dong, Yipeng; Yu, Tiannan; Wang, Rujie; Gao, Yang; Li, Song; Nong, Shaojun; Li, Wenguang (Frontiers in Immunology, 2022)
Bladder cancer (BLCA) ranks the 10th most common form of cancer worldwide. Currently, the response rate of BLCA patients to novel immunotherapy and immune checkpoint inhibitors (ICIs) treatment is around 30% or less. Therefore, there is an urgent clinical demand to understand the regulation of immune function in BLCA patients. LncRNAs were known to play fundamental roles in the regulation of the immune system in tumor microenvironment. In this report, we performed comprehensive analysis to identify immune-related lncRNAs (IRLs) in BLCA patients using The Cancer Genome Atlas (TCGA) databases. BLCA patients were divided into five TME subtypes. Subtype HMIE was found to be strongly related with patients' survival and high anti-tumor activities. Through four-step analysis, we identified 34 IRLs as subtype HMIE related lncRNAs (HMIE-lncs).The correlation analysis with immune cell infiltration and target gene pathway enrichment showed that 34 HMIE-lncs were correlated with immune cell activation and tumor cell killing. Among them, 24 lncRNAs are related to good prognosis. We constructed a risk model to predict BLCA. Cross tumor validation was performed and the results showed that the 34 HMIE-lncs identified in the BLCA patients in this study were highly expressed in immune-favorable TME subtype (IE) in most of other cancer types.